Development of a Traditional Game Module to Improve Children's Self-Control Character Skills - Liswantiani, Ester; Wibowo, Setiawan Edi; Nugrahanta, Gregorius Ari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research intends to guide teachers in developing self-control in children aged 9-12 through traditional games. The research method used was Research and Development (R&D) with the ADDIE framework (Analyze, Design, Develop, Implement, and Evaluate) involving six teachers, seven module validators, and six children. The research findings are as follows: The module received a